DETERMINANTS OF MARKETING INNOVATIONS IMPLEMENTATION AMONG MSMES IN RESOURCE-CONSTRAINED ENVIRONMENTS: EVIDENCE FROM NORTHEAST NIGERIA (UNIZIK Journal of Marketing, 2026)
Marketing innovation is increasingly recognized as a cost-effective strategy for MSMEs in resourceconstrained environments. However, limited attention has been given to the drivers that enable its implementation in such contexts. This study examines the determinants of marketing innovation implementation among micro, small and medium enterprises (MSMEs) in Northeast Nigeria. Specifically, it investigates the influence of entrepreneurial orientation, digital capability and market intelligence capability on marketing innovation implementation among registered MSMEs in Bauchi, Gombe, and Borno States. A cross-sectional survey design was adopted. The population comprised 73,327 MSMEs, from which a minimum sample size of 398 was derived using the formula proposed by . To address potential non-response, the sample was increased by 10% in line with methodological recommendations of , yielding a final sample of 438. Bowley’s proportional allocation and a multistage sampling technique were employed to ensure representativeness. Data were collected via structured questionnaires and analyzed using multiple regressions. Findings reveal that entrepreneurial orientation, digital capability and market intelligence capability have significant positive effects on marketing innovation implementation. The study concludes that firm-level capabilities drive marketing innovation in resource-constrained environments. It recommends that MSMEs strengthen entrepreneurial orientation, invest in digital capabilities and enhance market intelligence to improve innovation outcomes and competitiveness.
Keywords: marketing innovation, entrepreneurial orientation, digital capability, market intelligence capability, MSMEs, resource-constrained environments